Germination and Seedling Characters of Different Wheat Cultivars under Salinity Stress - A.A. Kandil; A.E. Sharief; M.A. Elokda (Journal of Basic & Applied Sciences, 2012)
The impact of salt stress under different salinity level (2, 4, 6, 8, 10, 12 and 14 dS/m-1 NaCl) on eleven varieties of bread wheat (Triticum aestivum L.) viz., Sakha 93, Gemmeza 7, Egaseed 7, Sakha 94, Gemmeza 10, Egaseed 3, Masr 2, Masr 1, Gemmeza 9, Sids 1 and Giza 168 was conducted. A laboratory experiment was conducted at Giza Central Seed Testing laboratory of Central Administration for Seed Testing and Certification, Ministry of Agriculture, Egypt. Wheat cultivars significantly varied in means of final germination percentage, germination rate, germination index, vigor index, shoot length, root length, shoot fresh weight, root fresh weight, shoot dry weight, root dry weight, seedling height reduction and relative dry weight. Sakha 93 and Sakha 94 had positive effects in most of studied characters while, Masr 1 cultivar had negative effects in most of germination parameters under study. Salinity concentrations significantly varied in all germination parameters under study except shoot dry weight character. Increasing salinity concentrations from 0 to 14 dS/m-1 gradually decreased average of germination and seedling characters. All studied characters were significantly affected by the interaction between cultivars and salinity stress, vice versa, root length didn’t affect by the interaction. It could be concluded that for maximizing wheat germination percentage and seedling parameters under salinity stress are recognized by using Sakha 93, Sakha 94 and Gemmeza 10 cultivars with increasing salinity concentrations levels up to 14 dS/m-1. Among the cultivars under investigation Sakha 93 and Sakha 94 cultivars appeared to be more tolerant to salinity at germination stage compared with other cultivars. These cultivars were more tolerant to salinity and recommended to use in breeding program for enhancing Wheat production in Egypt.